Antimalarial activity of goat bile against Plasmodium berghei ANKA infection in BALB/c mice - Kholida Nur Aini; Windya Tri Hapsari; Kartika Arum Wardani; Heny Arwati; Willy Sandhika (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
Abstract Goat bile has been used by some Indonesian people to treat malaria and increase their stamina. This study aimed to prove whether goat bile toxic or not in BALB/c mice and to verify the antimalarial activity of goat bile at various concentrations in mice infected with Plasmodium berghei ANKA. Acute toxicity test was performed using twenty male BALB/c mice with an average body weight of 25 grams, which were divided into four groups. Mice were given 25%, 50%, and 100% goat bile, respectively, while negative control was given distilled water. Any change in weight, odor, color, agitation, appearance, color of urine and feces, coma, and death, were recorded. A different set of mice were infected with P. berghei ANKA. This study conducted using the posttest only control group design with four treatments and five replications. A four day-treatment of goat bile was given by oral gavage to find out its effect on parasitemia level. Infected mice were divided randomly into 4 groups, where the GBNeg group as negative control was given only distilled water. The GB25, GB50, and GB100 groups were treated with 25%, 50%, and 100% goat bile, respectively. The parasitemia was observed daily on Giemsa-stained tail blood smears of each mice. No death or other sign of toxicity was found in goat bile-treated mice. Goat bile showed anti-malarial activity. The parasitemia in all goat bile treated groups was lower compared with the negative control group. The ED50 of goat bile against the growth of parasite was 48,55 %. Goat bile is a potential source of new antimalarial therapies. Further investigations are recommended to yield new anti-malarial drug candidates. Keywords                :    Goat bile, parasitemia, Plasmodium berghei ANKA, ED50Correspondence     :    heny-a@fk.unair.ac.id